Malignant Presentation of Benign Tumour of the Rectum - Sanjeev Sandrasecra; Sindhu Karpayah; Nornazirah Azizan; Muhammad Ash-Shafhawi Adznan; Firdaus Hayati; Rohamini Sibin (2020)
Rectal schwannomas are rare mesenchymal tumour of the gastrointestinal tract. They are scarcely identified in the low rectum as compared to the proximal tract. If present, huge tumour tends to be symptomatic leading to obstruction, bleeding, and tenesmus. We highlight a 74-year-old man with malignant presentations mimicking low rectal cancer. Colonoscopy revealed a huge pedunculated polyp measuring 10 x 8 cm with a diagnosis of benign tumour of schwannoma upon punch biopsy. Transanal excision was made after failure of endoscopic resection. Microscopic evaluation of the tumour showed a benign nerve sheath tumour of schwannoma supported by positive S100 protein expression. His recovery was excellent, hence he was discharged on the following day. There are no similar symptoms and tumour recurrence on follow up. A huge rectal tumour is not always malignant. Despite their rarity, schwannomas can manifest as malignant features. In case of tumour that mimics rectal carcinoma, preoperative diagnosis is very important for a management plan. The definitive histological diagnosis is based on the morphological features with diffuse positivity of S100 from immunohistochemical study. Surgical resection either endoscopic or transanal approach is the mainstay of treatment, especially when dealing with local complication caused by the huge bulk of tumour.